The Current Status of Ethnobiology in Ecuador - Tania Ivanova Gonzalez-Rivadeneira; Radamés Villagómez-Resendiz; Alessio Barili (Ethnobiology Letters, 2018)
This article gives an account of the current status of ethnobiology in Ecuador. Our goal is a generalized diagnosis of Latin America’s ethnobiological research production, which portrays Ecuadorian ethnobiology as practically non-existent. We perform an updated search of online databases, using a range of keywords, to show that elements of an ethnobiological research program are indeed present in Ecuadorian scholarship. While ethnobotany is the most developed sub-discipline of ethnobiology in Ecuador, there is also research on ethnomedicine, ethnozoology, and, to a lesser extent, ethnomycology. The development of these sub-disciplines promotes further ethnobiological scholarship in Ecuador. Beyond these sub-disciplines, ethnobiology is interwoven with contemporary anthropological accounts that emphasize the relationships between nature and culture and shine a light on the epistemic plurality of ethnobiology. If ethnobiology in Ecuador is distinguished by an epistemic plurality—understood through these different styles of reasoning—then it can be characterized without being confined to sub-disciplines with the ethno- prefix.